Financial Accountability and Sustainability of Islamic Social Finance: Empirical Evidence from Zakat Management - Haris, Abdul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines the role of financial accountability in supporting the sustainability of Islamic Social Finance within zakat management in Indonesia. The research is motivated by the limited transparency of zakat institutions, where only a small proportion publicly disclose audited financial statements despite the large number of registered institutions. Using a quantitative, descriptive–empirical approach, this study analyzes secondary data from audited financial reports of zakat institutions that disclose their financial information on official websites. Financial accountability is assessed through indicators of transparency, audit status, and key financial ratios, while sustainability is reflected in zakat distribution performance, fundraising dynamics, and growth trends. The analysis reveals substantial variation in accountability practices across institutions, indicating that transparency and reliable financial reporting are not yet institutionalized as common governance standards. The findings further demonstrate that zakat institutions with higher levels of financial accountability tend to exhibit more stable distribution patterns and more sustainable fundraising performance. In contrast, institutions with limited disclosure face greater risks of operational instability. These results suggest that financial accountability functions not only as a compliance mechanism but also as a strategic foundation for sustaining zakat management over time. This study contributes to the Islamic Social Finance literature by providing empirical evidence on the relationship between accountability and sustainability using publicly disclosed audited data, and it offers practical insights for policymakers and zakat managers in strengthening governance frameworks to enhance public trust and ensure long-term sustainability.